Factors Affecting Access to Healthcare: An Observational Study of Children under 5 Years of Age Presenting to a Rural Gambian Primary Healthcare Centre. - Claire P Rees; Sophie Hawkesworth; Sophie E Moore; Bai L Dondeh; Stefan A Unger (PLoS ONE)
Main objective Prompt access to primary healthcare before onset of severe illness is vital to improve morbidity and mortality rates. The Gambia has high rates of child mortality and research is needed to investigate contributing factors further. This study aimed to identify factors affecting access to primary healthcare for children <5 years (y) in rural Gambia focusing on delayed presentation and severe illness at presentation as indicators in a setting where primary healthcare is delivered free of charge. Methods Data were extracted from an electronic medical records system at a rural primary healthcare clinic in The Gambia for children (0-5y) between 2009 and 2012. First clinic attendances with malaria, lower respiratory tract infections (LRTI) and diarrhoeal disease, the main contributors to mortality in this setting, were identified and categorized as delayed/non-delayed and severe/non-severe representing our two main outcome measures. Potential explanatory variables, identified through a comprehensive literature review were obtained from an ongoing demographic surveillance system for this population. Variables associated with either delayed/non-delayed and/or with severe/non-severe presentations identified by univariate analysis (p<0.1) were assessed in multivariate models using logistic regression (p<0.05). Results Out of 6554 clinic attendances, 571 relevant attendances were identified. Delayed presentation was common (45% of all presentations) and there was a significantly reduced risk associated with being from villages with free regular access to transport (OR 0.502, 95%CI[0.310, 0.814], p = 0.005). Children from villages with free regular transport were also less likely to present with severe illness (OR 0.557, 95%CI[0.325, 0.954], p = 0.033). Conclusions Transport availability rather than distance to health clinic is an important barrier to accessing healthcare for children in The Gambia, and public health interventions should aim to reduce this barrier.